State of the art of the effective flange width for composite T-beams. (30th May 2020) - Masoudnia, Reza
Abstract: Composite T-beams represent an efficient and economical structural beam element for a wide range of structural applications. A T-beam subjected to a positive bending moment results in part of the slab acting as the flange of the girder and resisting compression. When the spacing between the girders becomes large, shear-lag phenomena lead to compressive stresses in the flange that vary with the distance from the girder web and the flange area over the web becomes more highly stressed than the extremities. These phenomena lead to inaccurate structural analyses. Therefore, the effective flange width concept has been introduced for design purposes.